Commissive Speech Acts in Political Discourse of the Merah Putih Cabinet Meeting Video - Bimo Ramadhani Samudra; Harun Joko Prayitno (Universitas Nusantara PGRI Kediri, 2026)
This study aims to examine the forms and functions of commissive speech acts in political discourse found in live broadcast videos of the Red and White Cabinet Meeting uploaded on YouTube. Using a qualitative descriptive approach, the research focuses on utterances containing commissive speech acts delivered by meeting participants during the sessions. Data collection was conducted through observation and note-taking, while data analysis applied Charles Morris’s pragmalinguistic model, including data collection, categorization, analysis, and conclusion drawing. The results reveal 20 instances of commissive speech acts, consisting of promises (45%), intentions (25%), offers (10%), and guarantees (20%). Promises and intentions are the most dominant, functioning to provide certainty, demonstrate commitment, reassure, and build public trust. Offer speech acts are used to propose policies, whereas guarantees aim to convince interlocutors and the public about the continuity of government programs. These findings indicate that commissive speech acts play a strategic role in political communication to strengthen legitimacy, commitment, and trust. The study further suggests that the use of commissive speech acts in digital spaces serves as an instrument for public accountability.